APLICAÇÃO DOS PROGRAMAS "CORELE", "ACP" E "PIPOUST" NO ESTUDO DAS ÁGUAS DAS FONTES (ÁGUAS DA PRATA, EST. DE SÃO PAULO) - Szikszay, M.; Teissedre, J. M. (Águas Subterrâneas, 1982)
Resumo não disponível.